A quantitative study of the influence of fixation on immunoperoxidase staining of rectal mucosal plasma cells. Issue 4 (April 1980) - Piris, J; Thomas, N D
Abstract : A quantitative morphometric study of the immunoglobulin-containing plasma cells in rectal biopsies from nine patients with ulcerative colitis and three patients with the irritable colon syndrome is presented. The results show that fixation of the biopsy specimens with formol-sublimate, a mercuric fixative, resulted in better staining with the immunoperoxidase method and that, by comparison with formol saline, higher cell counts were always obtained.